2010
DOI: 10.1182/blood-2010-02-269621
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide improves event-free and overall survival for adults with acute promyelocytic leukemia: North American Leukemia Intergroup Study C9710

Abstract: Arsenic trioxide (As 2 O 3 ) is a highly effective treatment for patients with relapsed acute promyelocytic leukemia (APL); its role as consolidation treatment for patients in first remission has not been defined. We randomized 481 patients (age > 15 years) with untreated APL to either a standard induction regimen of tretinoin, cytarabine, and daunorubicin, followed by 2 courses of consolidation therapy with tretinoin plus daunorubicin, or to the same induction and consolidation regimen plus two 25-day courses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
289
4
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 332 publications
(311 citation statements)
references
References 28 publications
16
289
4
2
Order By: Relevance
“…According to the recent data of this important trial (Leukemia Intergroup Study C9710), the addition of ATO is an important improvement to the treatment strategy since the 3-year EFS reached 80%, 76 which is consistent with our point of view that the treatment of APL should target both PML and RARa to fulfill a maximum efficacy. In this study, both of the two randomized groups were given the same induction therapy (ATRA, Ara-C and daunorubicin).…”
Section: Consolidation Therapysupporting
confidence: 82%
“…According to the recent data of this important trial (Leukemia Intergroup Study C9710), the addition of ATO is an important improvement to the treatment strategy since the 3-year EFS reached 80%, 76 which is consistent with our point of view that the treatment of APL should target both PML and RARa to fulfill a maximum efficacy. In this study, both of the two randomized groups were given the same induction therapy (ATRA, Ara-C and daunorubicin).…”
Section: Consolidation Therapysupporting
confidence: 82%
“…Based on these experiences and the results of single agent anti-APL efficacies of ATRA and arsenic trioxide [59], investigators evaluated the addition of ATRA to chemotherapy during both induction and/or consolidation [60][61][62], the addition of arsenic trioxide during consolidation therapy [63], and the use of nonchemotherapy regimens including ATRA, arsenic trioxide, and GO. Comparative studies showed that the addition of ATRA to chemotherapy during induction and or consolidation improved survival [60][61][62], and that the addition of arsenic trioxide during consolidation in CR also improved survival.…”
Section: Acute Promyelocytic Leukemiamentioning
confidence: 99%
“…Unlike the other regimens, the APML4 trial does not use cytarabine during induction. In light of these new studies, the panel recommends initial induction with ATRA plus daunorubicin and cytarabine 81,83,84 ; ATRA plus idarubicin alone 85 ; ATRA plus idarubicin and ATO 100 ; or enrollment in a clinical trial. In addition, the panel recommends the administration of prophylactic corticosteroids (eg, dexamethasone) in patients with a WBC count greater than 10,000/mcL (or in patients receiving induction with both ATRA and ATO, regardless of WBC count) to prevent differentiation syndrome (see Supportive Care on page AML-C).…”
Section: Nccn Guidelines Version 22014 Acute Myeloid Leukemiamentioning
confidence: 99%
“…84 In this trial, patients who were randomized to receive 2 courses of 25 days of ATO (5 days a week for 5 weeks) immediately after entering CR and NCCN Guidelines Index AML Table of Contents Discussion…”
Section: Consolidation Therapy For Patients With Aplmentioning
confidence: 99%
See 1 more Smart Citation